2005
DOI: 10.1542/peds.2004-2066
|View full text |Cite
|
Sign up to set email alerts
|

Diaper Dye Dermatitis

Abstract: ABSTRACT. Diaper dermatitis is a common problem in outpatient pediatric office settings. Although most diaper rashes represent a form of contact dermatitis in response to irritants in the diaper environment, other rashes may be the result of an allergen in the diaper. On the basis of clinical examination results for 5 patients and patch testing results for 2 patients, we suspect that the patients demonstrated allergic contact dermatitis in response to the various blue, pink, and green dyes in diapers. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…Bazen de¤iflik lezyonlar fiili livata bulgular›n› taklit edebilir. Bu lezyonlar aras›nda deri ve mukozada k›zar›kl›k (hiperemi) ve renk de¤iflikli¤i (Mongol lekeleri), kanama (Henoch Schönlein Purpuras›), soyulma bulunan tablolar, nikel, çocuk bezi materyali ya da bezin boya içerik-lerine alerjiler, selülit, fitodermatit, venöz konjesyon, anormal anatomik yap›, anal fissürler, anal dilatasyon, lichen sclerosis, büllöz hastal›klar/vulvar pemfigoid, hemanjioma, sarkom say›labilir (1,5,(7)(8)(9).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bazen de¤iflik lezyonlar fiili livata bulgular›n› taklit edebilir. Bu lezyonlar aras›nda deri ve mukozada k›zar›kl›k (hiperemi) ve renk de¤iflikli¤i (Mongol lekeleri), kanama (Henoch Schönlein Purpuras›), soyulma bulunan tablolar, nikel, çocuk bezi materyali ya da bezin boya içerik-lerine alerjiler, selülit, fitodermatit, venöz konjesyon, anormal anatomik yap›, anal fissürler, anal dilatasyon, lichen sclerosis, büllöz hastal›klar/vulvar pemfigoid, hemanjioma, sarkom say›labilir (1,5,(7)(8)(9).…”
Section: Discussionunclassified
“…Bir çeflit kontakt dermatiti olup, derinin irritasyon, nem, kimyasallar, idrar ve gaitaya karfl› verdi¤i nonimmünolojik bir reaksiyondur. Basit bir k›zar›kl›ktan ödemli eritematöz papüllere kadar olan çeflitli formlarda gözlenebilmektedir (9,11).…”
Section: Tartifimaunclassified
“…Consumer research has indicated a preference for use of colors that make diapers appear to resemble underwear, and safety evaluations have shown that, as used, the colors used in diapers should not cause irritation or dermatitis (Table 1). 11 Despite the common misconception and previous concerns, 12 the colors in disposable diapers are pigments, not disperse dyes. 13 Pigments are very large molecules that do not absorb moisture when wet and are not known to cause skin irritation or sensitization based on standard toxicological tests.…”
Section: Common Ingredients Found In Disposable Diapersmentioning
confidence: 99%
“…6 Allergic contact dermatitis usually develops when new products are introduced. 7 It can involve any skin to which the agent is applied, including sites outside the diaper area on the trunk, extremities, and face.…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%